U.S. Bishops in the Public Square: Prophets or Pilgrims ? - Winters, Michael (Laval théologique et philosophique, 2015)
In this paper, it will be argued that there are two dominant styles of leadership which dominate in the United States today : one is the style of the culture warrior, who takes a defensive posture towards the dominant culture ; the other, more traditional, is that of the churchman, who teaches what the Church teaches, but lets the laity engage that teaching in the culture.